PROCESSOS DE SUBJETIVAÇÃO: Das relações de poder à ética do cuidado de si - CARVALHO, Elinalva Pinto de (2024)
"What to make of ourselves? This question presents, in Michel Foucault's thought, an important indication of his philosophy, primarily to understand, in his later writings, how the philosopher diagnoses our present times. Such formulation implies investigating the configuration of power devices and their mode of governance, the purpose of which unfolds in shaping the relationship individuals have with themselves. As, for the French in the mid-18th century, mechanisms of control centered on the body-species were developed, meaning the subject is immersed in the technologies of discipline, surveillance, and biopolitical management. Under these propositions, the philosopher establishes the question of the subject constituting itself in the interlacing of power and knowledge games. From this perspective, in problematizing power relations, Foucault urges us to rethink and redefine our own conception of power in modern societies, which establish ways of living and being. However, power relations for Foucault do not function merely as a negative position but constitute a perspective of resistance, which materializes as action upon actions. In this dispute, the work is grounded in the discussion aimed at considering ethics in Foucauldian research. To this end, we trace the concepts of care of the self and aesthetics of existence in the context that reflects the agonistic position of the subject with oneself as a possibility of self-constitution. Thus, we detach ourselves to investigate the ethical problem of the subject from the relations between knowledge and power, with emphasis on the processes of subjectivation, which implies an incision that we can make of the technology of power observed by Foucault, where subjectification and freedom intersect.